The Relationship Between Social Sustainability Practices and Performance Outcomes in Supply Chain Management: The Case of Vietnam - Ngoc Hong Duong; Thanh Trang Bui; Quang-An Ha (SAGE Open)
Nowadays, both academic scholars and decision makers are raising much attentions to underscore the meanings of social sustainability practices to the success of firms, particularly in the context of emerging countries. Under the stakeholder resource-based view (SRBV) theory, the current research model was adopted to identify determinants of social sustainability practices and its linkages with performance outcomes of the supply chain. There were 204 valid samples collected from respondents who operate the supply chains in the Vietnamese medium and large enterprises. Empirical results indicated that social sustainability practices positively impact on the performance outcomes of the supply chain management. Critically, this study is among the very first-ever papers that significantly evidenced the mediating roles of customer performance and supplier performance in the relationship between a firm’s social sustainability practices and supply chain performance. The multidimensional concept of social sustainability has been extendedly incorporated in the context of Vietnamese companies, it provides managers and policy-makers useful insights for implementing social sustainability in the corporate sustainable development strategies.